A nationwide, prospective collection of patient reported outcomes in the Cancer Registry of Norway - Ylva Maria Gjelsvik; Tom Børge Johannesen; Giske Ursin; Tor Åge Myklebust (Norsk Epidemiologi, 2022)
Background: The Cancer Registry of Norway (CRN) has collected data on all Norwegian cancer patients from health providers since 1952. To assess cancer patients’ self-reported late effects and health related quality of life(HRQoL) after treatment, the CRN started collecting data on Patient Reported Outcomes (PROs) in 2020.